UPAYA MENINGKATKAN PASSING BOLA VOLI MENGGUNAKAN METODE PEMBELAJARAN DEMONSTRASI PADA SISWA KELAS V UPT SPF SDI KAMPUS IKIP - Nurhikma Amal; Rahmad Risan (Jurusan Pendidikan Teknik Elektro, 2024)
This study aims to enhance volleyball passing learning outcomes using the demonstration method, thereby improving student learning quality. The research, employing classroom action research, focused on fifth grade students at UPT SPF SDI KAMPUS IKIP. Data was collected across two cycles, with performance test results serving as the primary instrument. Results showed significant improvements between cycle 1 (75.33%) and cycle 2 (100%), demonstrating a 24.67% increase. The study concludes that the demonstration method effectively enhances volleyball passing learning outcomes for fifth grade students at UPT SPF SDI KAMPUS IKIP, suggesting its adoption by physical education teachers facing similar challenges in the Sekadau sub-district.